Assessing generative braille responding following training in a matching‐to‐sample format. Issue 4 (30th June 2016) - Putnam, Brittany C.; Tiger, Jeffrey H.
Abstract : We evaluated the effects of teaching sighted college students to select printed text letters given a braille sample stimulus in a matching‐to‐sample (MTS) format on the emergence of untrained (a) construction of print characters given braille samples, (b) construction of braille characters given print samples, (c) transcription of print characters given braille sample sentences, and (d) vocal reading given braille sample passages. The results demonstrated the generative development of these repertoires given MTS instruction.